SISTEM PAKAR DIAGNOSA PENYAKIT IBU MENYUSUI MENGGUNAKAN METODE FORWARD CHAINING DAN METODE CERTAINTY FACTOR - Abdul Rokhim; Ryan Wahyu Ramadhan (LPPM ITB Yadika Pasuruan, 2023)
Abstract: Breastfeeding is known as one of the most powerful influences on a child's survival. Breastfeeding provides many benefits, including functioning as a natural contraceptive for mothers, maintaining maternal health and saving family expenses. However, there are some common obstacles faced by breastfeeding mothers, one of which is the lack of prompt consultation services. Limited access of breastfeeding mothers to counseling with health workers regarding physical difficulties and complaints during breastfeeding. Therefore, this study aims to measure the level of risk using an expert system with the certainty factor method with web-based forward chaining tracing. This method is expected to help provide solutions and make it easier to detect diseases inbreastfeeding mothers. Â Â